Virtutes apostolorum: Editorial Problems and Principles - Rose, Els (Apocrypha, 2012)
Abstract The school of New Philology urges us as editors of medieval texts to take into account variance as a core characteristic of medieval manuscript transmissions. The scope of variance, however, remains unclear in the programmatic studies presented by this trend, which concentrates mainly on linguistic variants. Therefore, an elaborate methodology to incorporate variance in our editorial work still needs to be developed. It is the aim of this article to present a set of propositions in preparation of an edition of the Latin transmission of the Virtutes apostolorum, in order to add to the development of this methodology. The spectrum of variance in the Virtutes apostolorum as a series embraces textual variants ; variants concerning the presentation of the text at the level of the individual sections dedicated to one apostle (order of the apostles, choice of text, choice of redaction) ; variants in (the presence of) paratexts (titles, chapter titles, prologues, epilogues) ; variants caused by the manual transmission of these texts (corrections, uncorrected errors) ; and variants inserted by the users/readers of the series (semantic glosses, both vernacular and Latin, marginal glosses indicating liturgical use, stress marks on words for the benefi t of oral performance). The analyses show the great diversity in the preserved manuscripts. The main question will be how we can create an edition of such a complex and composite medieval text transmission so that its fluidity and variability become visible, as well as its use in medieval religious practice. Abstract L’École de la Nouvelle Philologie défend le retour aux manuscrits ainsi que l’attention aux variantes dans la transmission manuscrite des textes. Cependant, l’idée de ‘‘variante’’ est souvent limitée aux variantes textuelles, tandis qu’il y a d’autres sortes de variantes qui témoignent aussi de spécificités ainsi que des différents usages qui ont été faits des manuscrits. Le présent article examine la transmission latine des Virtutes apostolorum dans le monde médiéval. Dans cet ensemble de textes, plusieurs sortes de variantes sont analysées : variantes textuelles, variantes dans la présentation du texte au niveau des sections individuelles dédiées à un apôtre (ordre des apôtres, choix des textes, choix des rédactions), variantes dans les paratextes (titres, titres des chapitres, prologues, épilogues), variantes causées par la transmission (corrections et passages fautifs mais non corrigés), variantes créées par l’usage des textes (gloses vernaculaires et latines, gloses marginales indiquant l’usage liturgique, signes d’accentuation). Les analyses attestent de la grande diversité des manuscrits conservés. La question principale est de savoir comment éviter que l’édition des Virtutes apostolorum ne fournisse une présentation trop statique d’une tradition textuelle complexe et composite, et comment faire pour qu’elle atteste la variabilité qui caractérise ces textes, de même que l’usage de ces textes dans la pratique religieuse du Moyen Age.